Polymorphisms in CXCR3 ligands predict early CXCL9 recovery and severe chronic GVHD - Dai, Hao; Rachakonda, Sivaramakrishna P.; Penack, Olaf; Blau, Igor W.; Blau, Olga; Radujkovic, Aleksandar; Müller-Tidow, Carsten; Dreger, Peter; Kumar, Rajiv; Luft, Thomas (Blood cancer journal (New York), 2021)
Chronic graft-versus-host disease (cGVHD) is a major cause of mortality and morbidity after allogeneic stem cell transplantation (alloSCT). The individual risk of severe cGVHD remains difficult to predict and may involve CXCR3 ligands. This study investigated the role of single-nucleotide polymorphisms (SNPs) of CXCL4, CXCL9, CXCL10, and CXCL11, and their day +28 serum levels, in cGVHD pathogenesis. Eighteen CXCR3 and CXCL4, CXCL9–11 SNPs as well as peri-transplant CXCL9–11 serum levels were analyzed in 688 patients without (training cohort; n = 287) or with statin-based endothelial protection cohort ( n = 401). Clinical outcomes were correlated to serum levels and SNP status. Significant polymorphisms were further analyzed by luciferase reporter assays. Findings were validated in an independent cohort ( n = 202). A combined genetic risk comprising four CXCR3 ligand SNPs was significantly associated with increased risk of severe cGVHD in both training cohort (hazard ratio (HR) 2.48, 95% confidence interval (CI) 1.33–4.64, P = 0.004) and validation cohort (HR 2.95, 95% CI 1.56–5.58, P = 0.001). In reporter assays, significantly reduced suppressive effects of calcineurin inhibitors in constructs with variant alleles of rs884304 ( P < 0.001) and rs884004 ( P < 0.001) were observed. CXCL9 serum levels at day +28 after alloSCT correlated with both genetic risk and risk of severe cGVHD (HR 1.38, 95% CI 1.10–1.73, P = 0.006). This study identifies patients with high genetic risk to develop severe cGVHD.